Receiver mount design, transmitter depth, and wind speed affect detection probability of acoustic telemetry transmitters in a Missouri River tributary - Carlson, Tanner L.; LaBrie, Lindsey A. P.; Wesner, Jeff S.; Chipps, Steven R.; Coulter, Alison A.; Schall, Benjamin J. (Animal biotelemetry, 2023)
Background One of the most important considerations for acoustic telemetry study designs is detection probability between the transmitter and the receiver. Variation in environmental (i.e., wind and flow) and abiotic (i.e., bathymetry) conditions among aquatic systems can lead to differences in detection probability temporally or between systems. In this study we evaluate the effect of distance, receiver mount design, transmitter depth, and wind speed on detection probabilities of two models of acoustic transmitters in a mid-sized river. InnovaSea V16-6H (hereafter V16) and V13-1L (hereafter V13) tags were deployed in the James River, SD at 0.36 m (deep) and 2.29 m (V16 tag) or 1.98 m (V13 tag; shallow) above the benthic surface downstream of InnovaSea VR2W stationary receivers at distances of 100, 200, or 300 m. We used two receiver mount designs that included a fixed position within a PVC pipe on the downstream side of a bridge piling or a metal frame deployed in the middle of the river channel. Tags were deployed for 72 h at each location, and hourly detections were summarized. We evaluated downstream distance, receiver mount design, tag depth, and wind effects on tag detection using Bayesian logistic regression. Results Detection probability decreased as distance increased for all combinations of tag types and mount designs and varied from nearly 100% at 100 m to less than 10% at 300 m. The V16 transmitter had greater detection probability by the receiver mounted in the pipe than in the midriver frame. For both mounts, the deep V16 transmitter had greater detection probability than the V16 shallow transmitter. Detection probability of the V13 transmitter was similar between receiver mounts or transmitter depths. Wind speed had a negative impact on detection probabilities of both transmitter types and depths, except the deep V16 transmitter. Conclusions Deploying acoustic receivers in PVC pipes rather than midriver frames provided greater downstream detection probabilities for V16 transmitters under conditions evaluated in this study. In addition, V16 transmitters had greater detection probabilities when positioned deep within the water column rather than near the surface. We also demonstrated that wind speed can have a negative impact on detection probabilities.